Cold‐evoked potentials – Ready for clinical use?. (5th June 2016) - Hüllemann, P.; Nerdal, A.; Binder, A.; Helfert, S.; Reimer, M.; Baron, R.
Abstract: Background: Cold‐evoked potentials (CEPs) are known to assess the integrity of A‐delta fibres and the spinothalamic tract. Nevertheless, the clinical value was not investigated previously. The aim of this study was to measure CEPs in 16 healthy subjects from the face, hand and foot sole and to investigate whether CEPs reliably detect A‐delta fibre abnormalities. Methods: Swift cold stimuli were applied to the skin with a commercially available thermode, which cooled down from 30 to 25 °C in approximately 0.5 s. CEP latencies (N1, N2 and P2) and amplitudes (N1, N2/P2) were recorded with EEG. Reversible A‐fibre function loss was induced by applying a selective A‐fibre block at the superficial radial nerve. Results: In all 16 subjects CEPs could be recorded from all locations; N2, P2 mean latencies were 276.4 ± 38.9 and 389.8 ± 52.5 (face), 318.6 ± 31.6 ms and 477.7 ± 43.6 (hand), and 627.6 ± 84.4 and 774.2 ± 94.0 (foot sole). N2/P2 amplitudes were 10.7 ± 4.1, 11.3 ± 4.1 and 7.5 ± 4.1 μV. During A‐fibre block no CEPs were detectable in the grand average, which restored 10 min after block removal. Conclusions: CEPs were reliably recorded in healthy subjects at the hand, face and foot. Experimentally induced reversible A‐delta fibre function loss was detected by CEPs. Functional recovery was assessed as well. This study is basis for further CEP evaluation studies and might be the first step for implementing CEPs in clinical routine for the early diagnosis of small‐fibre disease. What does this study add?: Cold‐evoked potentials are capable of reliably measuring A‐delta fibre integrity, loss of function and functional recovery in healthy subjects, which is an essential prerequisite for diagnostic use in patients with small‐fibre disease.